The glass universe [compact disc, unabridged] : how the ladies of the Harvard Observatory took the measure of the stars - Sobel, Dava (Penguin Audio, 2016)
Shares the story of the scientific contributions of a group of women working at the Harvard College Observatory from the late 1800s through the mid-twentieth century, tracing their collection of star observations captured nightly on glass photographic plates.